ENHANCING DIGITAL TRANSACTION LITERACY FOR THE COMMUNITY: STRATEGIES AND IMPACTS - Farida, Siti Afiata; Hendri Hermawan Adinugraha; M. Shulthoni (Journal of Management and Islamic Finance, 2024)
This research aims to analyze the role of digital transaction literacy in improving financial understanding among the public. In this research method, researchers used a descriptive qualitative approach with data collection techniques through documentation from various sources such as books, journals, and related literature. The results show that digital transaction literacy plays an important role in improving people's understanding of online transactions, including understanding the basic concepts of online transactions, transaction security, consumer rights, technical skills, and attitudes and behaviors towards the use of digital technology. The implication of this research is the importance of digital transaction literacy socialization efforts, such as the National Non-Cash Movement (GNNT) program, to increase the understanding and use of non-cash transactions at all levels of society. Thus, this study contributes to expanding the understanding of the importance of digital transaction literacy and socialization efforts in improving the understanding and use of non-cash transactions in society, which in turn can make a positive contribution to the national economy. Keywords: Digital literacy, Digital transactions, Improvement, and Socialization of digital transaction literacy.